2009
DOI: 10.1016/j.marenvres.2008.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Tidal height influences the levels of enzymatic antioxidant defences in Mytilus edulis

Abstract: We investigated the potential variability of enzymatic antioxidant activities in blue mussels Mytilus edulis from a single intertidal population but living at different tidal heights. Activity levels of antioxidant enzymes (Cu/Zn superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase, glutathione transferase) were measured in the gills and digestive gland of mussels sampled at high shore (HS, air-exposure>6h/12h) and low shore (LS, air-exposure<2h/12h) of an intertidal zone (Yport, Norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 38 publications
(46 reference statements)
2
18
1
Order By: Relevance
“…This was in contrast with the findings in a similar study by Letendre et al (2009), where higher GST activity was found in the digestive gland from high shore mussels compared to mussels sampled from the low shore. However as Letendre et al (2009) and other studies (Manduzio et al, 2004;Power and Sheehan, 1996) stated, a tissue-specific role has to be considered for the GST activity with a generally higher and more variable expression found in gill tissues than in the digestive gland (Manduzio et al, 2004;Power and Sheehan, 1996). Nevertheless, the GST activity from this study (median ¼ 0.007) was similar to the GST activity level (median ¼ 0.010) measured from a variety of low pollution impact sites throughout the northern hemisphere .…”
Section: Around Ireland and In Parts Of The United Kingdom And Francecontrasting
confidence: 99%
See 2 more Smart Citations
“…This was in contrast with the findings in a similar study by Letendre et al (2009), where higher GST activity was found in the digestive gland from high shore mussels compared to mussels sampled from the low shore. However as Letendre et al (2009) and other studies (Manduzio et al, 2004;Power and Sheehan, 1996) stated, a tissue-specific role has to be considered for the GST activity with a generally higher and more variable expression found in gill tissues than in the digestive gland (Manduzio et al, 2004;Power and Sheehan, 1996). Nevertheless, the GST activity from this study (median ¼ 0.007) was similar to the GST activity level (median ¼ 0.010) measured from a variety of low pollution impact sites throughout the northern hemisphere .…”
Section: Around Ireland and In Parts Of The United Kingdom And Francecontrasting
confidence: 99%
“…In conclusion, the range of the natural factors which can influence the defence mechanisms in intertidal and cultivated mussels is highly complex, however this study provides an insight into the spatial variability of biomarkers of stress and damage using blue mussels. Our results support the conclusions of Letendre et al (2009) that the location of organisms on the shore should be taken into account in sampling for ecotoxicological studies and that environmental conditions may affect antioxidant responses in mussels. In addition this study provides a comprehensive overview of commonly used suite of biomarkers of stress, damage and reproduction.…”
Section: Around Ireland and In Parts Of The United Kingdom And Francesupporting
confidence: 88%
See 1 more Smart Citation
“…NanoZnO did not increase LPO at significant levels (α b 0.05), but a significant decrease between exposure to the highest concentration (i.e., 2.5 mg/L) of dissolved zinc and nanoZnO and 7 days of exposure to air was found, suggesting that normoxic conditions are required for LPO in mussels exposed to nanoparticles. The lack of LPO and peroxidase responses during air exposure could be explained by the increased activity of antioxidant enzymes (superoxide dismutase, catalase, glutathione peroxidase) when mussels are exposed to air during the first hours (Letendre et al, 2009). Inflammation could also be the result of bacterial growth during air exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, analysis of the oyster genome revealed an expansion of the genes coding for heat shock protein 70 and apoptosis inhibitors, which was interpreted as an adaptation to intertidal stressors (Zhang et al, 2012). One advantage of studying sessile organisms is that the same mussel assemblage can be sampled repeatedly over periods of days, weeks and even years, thus allowing phenotype to be interpreted within the context of both prevailing and prior abiotic events (Dowd et al, 2013;Gracey et al, 2008;Letendre et al, 2009;Regoli et al, 2004). This has made mussels particularly appropriate animals for investigating adaptive physiological processes that allow life to flourish in a fluctuating environment (Braby and Somero, 2006a;Fields et al, 2006;Hofmann and Somero, 1995;Logan et al, 2012;Williams and Somero, 1996).…”
Section: Introductionmentioning
confidence: 99%